Law Enforcement Against Illegal Logging as an Effort to Mitigate Climate Change: Case Study in the Mountain Ciremai Area - Swastika, Yurisa (KnE Social Sciences, 2025)
The environment is an essential and inseparable part of human life. Environmental degradation can also damage the habitats of surrounding flora and fauna, ultimately leading to extinction. Illegal logging causes both direct and indirect environmental damage. This study addresses two main research questions: how weak supervision and law enforcement regarding timber harvesting permit regulations contribute to the rise of illegal logging activities in the Mount Ciremai area, and how illegal logging laws are enforced in the region. This research employs a normative juridical method, which emphasizes legal norms and applicable regulations, as outlined in legislation relevant to the legal issues being studied. The study also involves interviews with the management of Mount Ciremai National Park (TNGC). The purpose of this research is to examine how law enforcement in Kuningan Regency, particularly in the Mount Ciremai area, responds to environmental damage caused by unauthorized tree cutting or illegal logging. Despite various meetings and discussions held to address the issue, the proposed action plans often failed to resolve the root causes. The lack of evidence and supporting materials remains a major challenge for the TNGC management. Therefore, this article is expected to contribute to policy considerations at both the regional and national levels.